Detection of Dengue Virus Serotypes in Aedes Mosquito Population from Sibu and Miri Divisions of Sarawak using Reverse Transcription Polymerase Chain Reaction (RT-PCR) - Harvie, Shukri (Universiti Malaysia Sarawak(UNIMAS), 2019)
Dengue has been a public health concern for many years in Malaysia. Having knowledge on the current circulating dengue serotype and population of vector mosquito is key in controlling outbreaks and future outbreak predictions. The current study reports the first study on detecting dengue virus serotypes in the Aedes mosquito population in Sibu and Miri divisions of Sarawak. Mosquito samples were collected at selected localities from September 2016 to December 2017. Localities were selected randomly mainly focussing on urban residential areas. The mosquitoes collected comprised of two types namely the field-caught adults and immatures collected from artificial and natural water containers. Collected mosquitoes were identified to species level and screened for presence of dengue virus and serotyped using conventional reverse transcription polymerase chain reaction (RT-PCR) and semi-nested PCR. Dengue virus serotype 2 (DENV-2) was identified in 3 pools of field-caught female Aedes albopictus adults that were collected from Jalan Tong Sang, Sibu, Sibu Lake Garden, and Taman Ceria, Permyjaya, Miri, respectively. DENV-2 was also detected in one pool of adult male Aedes albopictus that had emerged from immatures collected from Taman Ceria, Permyjaya, Miri. The findings in this study revealed that Aedes albopictus was the main species colonizing the study areas, and the current circulating dengue virus serotype is DENV-2. This study also reports the first natural evidence of transovarial transmission of dengue in the natural population of Aedes albopictus within the study area. This latest report may aid in providing information on establishing strategies in an effective vector control and, also to control any current and future outbreaks if necessary.